Post Earthquake Learning Assistance Strategy for Elementary School Students in Cibeureum Village, Cugenang District, Cianjur - Hotmaulina Sihotang; Erni Murniarti; Christina Metallica Samosir; Audra Jovani (Asian Journal of Community Services, 2023)
The Cianjur earthquake resulted in hundreds of deaths, minor to severe injuries, buildings destruction and landslides. Children studied in tents with appalling conditions. In addition, the impact of the earthquake that is even more serious is the emergence of trauma to children and adults. Before the earthquake happened, the children were cheerful and liked to play with their peers. The post-disaster turns the children’s feelings to gloom, quiet and afraid of the aftershocks' potential. The Directorate General of Higher Education, Research and Technology, which is involving Universitas Kristen Indonesia (UKI), is also overseeing the integrated community service (PkM) Incentive Program MBKM based on Key Performance Indicators (IKU) for Private Higher Education (PTS). The aim of the activity is to provide strength learning activity in the study tents and psychological healing for early childhood, kindergarten and elementary school students. The activities carried out are providing study tents and learning facilities, accompanying children by telling stories, playing games and ice breaking.